Numerical study on uniformity of temperature difference field in a spiral tube heat exchanger. (25th May 2021) - Cai, Hechang; Zhai, Yuling; Chen, Yao; Liu, Fanhan; Wang, Hua; Xu, Jianxin
Highlights: Two equations are developed to construct the temperature difference field. Two methods is proposed to measure the uniformity of continuous temperature field. The proposed methods can be applied for other real-world applications. New methods can characterize the heat transfer efficiency. Abstract: The characteristic of heat transfer of an organic working fluid driven by a built-in spiral low-temperature heat source is investigated numerically. Field synergy number is a function of the heat transfer factor j with the coefficient of correlation (r) all above 0.9. The temperature difference field is built based on the time space and position information about the objective. New metrics for quantifying the uniformity parameters of continuous temperature fields are developed by temperature difference field modeling. Those metrics are illustrated by using numerical modeling and present significant correlation between field synergy number or heat transfer factor. Furthermore, both the presented temperature field data and the other numerical temperature field is used to verify the effectiveness of this method. This method not only can significantly quantify variation on the uniformity of a temperature difference field under the same working conditions, but can also characterize the heat transfer efficiency at different times under the same working condition. This shows that the uniformity factor established in this study can reflect the heat transfer efficiency of heat exchanger as a whole, can be used as a new evaluation index of continuous field heat transfer efficiency, and can provide a new idea of the synthesis and optimization of heat exchanger.